Interactions with Projected Augmented Relief Models (PARM) - Arss, Nachnoer; Smith, Alastair D.; Priestnall, Gary (2017)
Techniques for enhancing physical landscape models with dynamic maps and imagery, termed Projected Augmented Relief Models (PARM), are part of a revival of interest in the power of relief models as tools for geographic visualization. This method enables the creation of dynamic and engaging public displays, which appear attractive but also promote discussion and interaction as revealed through direct observation and video. This paper explores the capabilities of physical relief models as tangible displays for geographic information, and considers the role of interaction using the Kinect sensor for finger detection. The focus of interaction is on making solid landscape models of real geographic areas reactive to touch.